A mild and efficient procedure for alkenols oxyselenocyclization by using ionic liquids. (2nd January 2019) - Kostić, Marina; Verdía, Pedro; Fernández‐Stefanuto, Verónica; Puchta, Ralph; Tojo, Emilia
Abstract: A mild and efficient procedure for the oxyselenocyclization of unsaturated alcohols by treatment with phenylselenyl chloride using ionic liquids as solvents/catalyzers has been developed. The reaction proceeds instantaneously under mild conditions with absolute regioselectivity, using primary, secondary, tertiary, and aromatic alcohols, as well as monosubstituted, disubstituted, and trisubstituted alkenols. This procedure provides a new method for the synthesis of substituted tetrahydrofurans and tetrahydropyrans ethers, the precursors of many biologically active metabolites, avoiding the use of toxic and corrosive catalysts. There are no previous reports of selenium‐mediated cyclofuncionalization reactions in ionic liquids. Taking into the account the good results obtained with [MMIM][MSO4 ], its ease preparation, low viscosity, low price, and its capacity to be recovered and reused, it was selected as the solvent/catalyzer. Quantum‐chemical calculations (MP2(fc)/6‐311 + G**//B3LYP/6‐311 + G**) has shown that the intramolecular cyclization is promoted by the hydrogen bond formed between the ionic liquid anion and the hydroxyl group of the alkenol. Abstract : A new mild and efficient procedure for the oxyselenocyclization of unsaturated alcohols using ionic liquids as solvents/catalyzers have been developed. The reaction proceeds instantaneously with absolute regioselectivity providing a new method for the synthesis of substituted tetrahydrofurans and tetrahydropyrans that avoids the use of toxis and corrosive catalysts. Mechanistic studies by quantum‐chemical calculations are decribed.